“Professor Catharine”. The culture of laughter at Vilnius University (Laughter, humour, satire, 2024)
In the first three decades of the 19th century, Vilnius was buzzing with humour and vibrancy, mainly due to the Vilnius Imperial University established in 1803. Imperial University of Vilnius. The community of laughter included Vilnius’ intellectual elite, students and social elites. Around 1815, Vilnius saw the appearance of the so-called Sheynekatarynka, a magic lamp that made a great impression on the city’s inhabitants. The memory of the characters depicted in it – professors of the Vilnius Academy – survived in the memoir literature of students: Edward Odyniec, Otto Sliźnia, Stanisław Morawski, Stanisław Małcużyński, Michał Czarnocki and Hipolit Klimaszewski. The humorous poems pointed out the flaws and weaknesses of the professorial body. They were also a criticism of the quality of university education.